Formulation and Antipyretic Evaluation of Papaya Root Extract (Carica papaya L.) Hydrogel Patch in Male Mice - Gabena Indrayani Dalimunthe; Zulmai Rani (Window of Health : Jurnal Kesehatan, 2026)
Papaya root (Carica papaya L.) has traditionally been used to manage fever, but its development as a standardized topical antipyretic preparation remains limited. Therefore, this study aimed to formulate hydrogel patches containing 5%, 10%, and 12.5% ethanolic papaya root extract and evaluate their physicochemical characteristics and antipyretic activity in DPT-HB vaccine-induced febrile male mice. Twenty-five mice (Mus musculus L.) were randomly allocated to a negative control, a positive control, and three extract-patch groups (n = 5 each). Rectal temperature was measured before fever induction and at 0, 15, 30, 45, and 60 minutes after treatment. Data were analyzed by one-way ANOVA followed by Tukey’s HSD test. All formulations were homogeneous, semi-solid, brownish patches with pH values of 5.7–5.8 and viscosities of 176,000–236,000 cP. At 60 minutes, temperatures were 38.2°C in the negative control, 36.9°C in the positive control, 36.7°C in the 5% group, 36.9°C in the 10% group, and 36.6°C in the 12.5% group. Significant differences were found among groups (p = 0.033), and the 12.5% formulation showed the largest observed temperature reduction. Papaya root extract can therefore be incorporated into a hydrogel patch with acceptable physicochemical characteristics and preliminary antipyretic activity.